Edible films based on aqueous emulsions of low-methoxyl pectin with recovered and purified sunflower waxes - Chalapud Narvaez, Mayra Carolina (2020)
BACKGROUND: Edible films were obtained from aqueous emulsions prepared with low-methoxyl pectin at different concentrations (10, 20 and 30 g kg−1) and two sunflower wax samples recovered from two waste samples of filter cakes produced in the winterization process of sunflower oil. The two sunflower waxes samples recovered (from the normal hybrid, NSFW, and from the high-oleic hybrid, HOSFW) were added in three proportions (0.1, 0.2 and 0.3 g g-1 of pectin). Films were evaluated according to their structure, water resistance, water vapor permeability, mechanical properties and thermal behavior. RESULTS: In general, good dispersion of the lipid material was observed in the cross-sections of the film. Increase in the water resistance (lower swelling index and water adsorption) was associated with a greater pectin content crosslinked with Ca2+ and the hydrophobic nature of waxes. The reduction in water vapor transfer rates was influenced by the effect of the wax addition, their fatty acid composition and their good distribution on the film. More resistant, rigid and less flexible films were obtained with lower pectin content, finding an inverse relationship between tensile strength and elongation percentage values. CONCLUSION: These results evidence a promising alternative in the development of innovative strategies to valorize sunflower waxes derived from waste material.